Using virtual reality to teach nursing students communication skills when breaking bad news: A focus group exploration of participant experiences (Journal of Applied Learning and Teaching, 2024)
Within higher education institutions, the use of virtual reality technologies has increased. However, while research is rich in the gaming and entertainment industries, the evidence within the field of undergraduate nursing is only just starting to emerge. The aim of this project was to explore 2nd-year undergraduate adult nursing students’ perceptions of using virtual reality as an adjunct to simulation teaching. Using a qualitative approach to enquiry and purposeful sampling, 17 students participated in one of 3 focus groups. Their responses were audio recorded, transcribed verbatim and analysed using thematic analysis. Data was independently coded and emerging themes, which were identified, were compared, and agreed upon by the research team. Four central themes emerged including fidelity, facilitation, facilities, and student learning, which have been incorporated into a multimodal pedagogical model. For successful implementation of this innovative teaching strategy, it is suggested that academics need to be cognisant of the study’s central themes, and how these interact and impact student satisfaction and levels of immersion.